Effect of nutritional supplements on the aquaporin-mediated oxidative stress - Lopes, Duarte Alexandre Ferrão (2021)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2018